Measuring the level of social self-efficacy and its relationship to some variables Among university students - Amira Abdul Karim Maran Hussein Al Marai ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The current study aimed to measure the level of social self-efficacy among the students of the University of Basra, and to measure the difference in the level according to the variables of gender, academic specialization, and marital status, and the relationship of these variables with the areas of social self-efficacy. The researcher used the measure of social self-efficacy, which was translated by the researcher (Youssef Al-Saud 2016), which consists of (16) items with five alternatives and paragraphs with a positive and negative direction, and after conducting psychometric steps on it. The results showed that there is an average level of social self-efficacy among university students, and there are no differences Statistically significant at a level of significance (0.05) with the variables of gender, academic specialization, and marital status. At the end of the research, the results were discussed and interpreted in light of the objectives of the current research, compared to the results of previous studies, and a number of conclusions, recommendations, and proposals to benefit from the current research and its future development by other researchers.